Commercialization of spirituality in the era of globalization - Abdul Razak, Mohd Abbas; Machouche, Salah (2022)
Despite all the sophistication in the areas of science and technology, modern man is in no way different from the one in the countryside, when faced with insurmountable psychological issues like stress, anxiety, depression, bereavement, etc. reaches out for a quick fix to resolve the matter. Mainly he hopes for some sort of divine intervention, a philosophy or a mind-control technique to get him out of his awful and pathetic condition. Seeing people in a desperate and vulnerable situation, fake gurus, spiritual healers, charlatan religious teachers and the likes exploit such human conditions to their benefit. The present study among others is geared toward exploring the different shades of meaning attached to the word spirituality, what are the underlying motives of the service providers, the techniques used to allure their clients, and how globalization helps in turning the service providers’ business into a lucrative one. Besides that, this study will also put forward some suggestions for those who are looking for a solution to overcome their psychological burdens. The research data of the study will be collected from literature, journal papers, and internet sources related to the interest of the study. As a qualitative study, in interpreting the relevant data of the study, the researchers will employ the content and textual analysis methods.